2017
DOI: 10.1016/j.healthpol.2017.07.007
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the mass media on obstetricians’ behavior in Norway

Abstract: Little is known about how physicians and hospitals respond to the risk of being negatively exposed in the mass media. We assume that newspapers will cover events more closely in the areas where they have most of their circulation. Within such areas the likelihood of negative publicity increases. The research question is whether obstetricians respond to negative newspaper coverage by choosing the least risky method of delivery, i.e. Caesarean section. This was tested on a large set of data from the Medical Birt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 51 publications
0
5
0
1
Order By: Relevance
“…47,48 Being sued (even if unsuccessfully) can generate negative publicity, damage reputations and professional confidence, and even destroy careers. [50][51][52][53] This situation may result in performing a CS for professional protection, rather than to benefit the mother and/or baby. 54 In some settings, most CS operations occur during working hours, and during weekdays, peaking on Fridays.…”
Section: Factors Related To Health Professionalsmentioning
confidence: 99%
“…47,48 Being sued (even if unsuccessfully) can generate negative publicity, damage reputations and professional confidence, and even destroy careers. [50][51][52][53] This situation may result in performing a CS for professional protection, rather than to benefit the mother and/or baby. 54 In some settings, most CS operations occur during working hours, and during weekdays, peaking on Fridays.…”
Section: Factors Related To Health Professionalsmentioning
confidence: 99%
“…The same authors repeated the study in Spain, on 1223 articles, with similar results, showing that less than 5% of the papers reported placenta praevia in the next pregnancy, infection or haemorrhage as side effects of CS [ 11 ]. A similar review explored the depiction of CS in 81 articles, 10 videos, six birth shows, two informational leaflets and one scientific paper across three countries whose CS rates were high (56%, in Cyprus), medium (36%, in Italy) and low (16%, in Iceland) [ 12 ]. The authors found that in Iceland, the media focus was on midwife-led care and normal birth, whereas in Cyprus and Italy, the media focussed more on the need to reduce the high rates of CS.…”
Section: Discussionmentioning
confidence: 99%
“…A study in Norway showed that gynecologists were susceptible to exposure to media since they cared for their reputation. These surgeons tended to be more likely to pursue defensive behaviors when the probability of negative promotions increased [34].…”
Section: Discussionmentioning
confidence: 99%